Behavioral outcomes of picky eating in childhood: a prospective study in the general population. (19th February 2016) - Cardona Cano, Sebastian; Hoek, Hans W.; van Hoeken, Daphne; de Barse, Lisanne M.; Jaddoe, Vincent W.V.; Verhulst, Frank C.; Tiemeier, Henning
Abstract : Background: Picky eaters in the general population form a heterogeneous group. It is important to differentiate between children with transient picky eating (PE) and persistent PE behavior when adverse outcomes are studied. We analyzed four PE trajectories to determine the associations with child mental health prospectively. Methods: From a population‐based cohort, 3, 748 participants were assessed for PE at 1.5, 3, and 6 years of age using maternal reports. Four trajectories were defined: persistent (PE at all ages); remitting (PE before 6 years only); late‐onset (PE at 6 years only); and never (no PE at any assessment). Child's problem behaviors were assessed with the Teacher's Report Form at 7 years of age. We examined associations between picky eating trajectories and emotional problems, behavioral problems and pervasive developmental problems using logistic regressions. Analyses were adjusted for child, parental, and socioeconomic confounders. We also adjusted for maternal‐reported baseline problem behavior at age 1.5 years; the never picky eating group was used as reference. Results: Persisting PE predicted pervasive developmental problems at age 7 years (OR = 2.00, 95% CI: 1.10–3.63). The association remained when adjusted for baseline pervasive developmental problems at 1.5 years (OR = 1.96, 95% CI: 1.10–3.51). Persistent PE was not associated with behavioral (OR = 0.92, 95% CI: 0.53–1.60) or emotional problems (OR = 1.24, 95% CI: 0.74–2.07). Other PE trajectories were not related to child behavioral or emotional problems. Conclusions: Persistent PE may be a symptom or sign of pervasive developmental problems, but is not predictive of other behavioral problems. Remitting PE was not associated with adverse mental health outcomes, which further indicates that it may be part of normal development.